High-Permittivity Polymer–Matrix Composites for the Development of Triboelectric Nanogenerators (TENGs) with Enhanced Performance: A Review - Urtecho, A.; Troncoso, O.P.; Torres, F.G. (Springer, 2024)
In recent years, the rapid increase in low-power electronics has shifted research focus towards new energy-harvesting devices. Triboelectric energy-harvesting technologies, such as triboelectric nanogenerators (TENGs), offer an efficient way to convert mechanical energy into electrical energy through the triboelectric effect. Polymers are used to fabricate crucial components in TENGs, acting as the triboelectric layers and storing electric charge. The dielectric properties of these polymers significantly influence the energy conversion capabilities of TENGs. High-permittivity polymer-based composites and nanocomposites have been studied for energy storage, such as capacitors, supercapacitors, and solar cells among others. These high-permittivity polymer composites can also be used to develop novel TENGs with high output performance. This paper reviews the development of high-dielectric-permittivity polymeric composites to be used as active triboelectric surfaces for TENGs with enhanced output performance. One strategy involves incorporating inorganic materials, semiconductors, conductors, and carbon-derived materials as an active phase within the polymer matrix. Other strategies, including the usage of polymeric fillers, coating, polarization, and ion implantation techniques, are also reported. This review may serve as a reference for optimizing polymer-based dielectrics in energy-harvesting-related areas. Through a deeper understanding of these techniques and materials, we can enhance the performance of TENGs to achieve high output efficiency.
Keywords: Polymer dielectrics; triboelectric nanogenerators; permittivity; dielectric constant; ceramic fillers; percolative polymer composites; https://purl.org/pe-repo/ocde/ford#2.05.01